Trillion game. Volume 6 - Inagaki, Riichiro (VIZ Media, LLC, 2025)
"Self-proclaimed 'world's greediest man' Haru and timid computer whiz Gaku set out to make a trillion dollars. They start the company Trillion Game to accomplish this task and hope to iron out the details as they go. With charm, technical skills, and no business plan, can these unlikely friends reach their lofty goal? Trillion Game Inc. is on the rise with a smash-hit mobile game! But what will Haru and Gaku do when President Kokuryu of Dragon Bank offers to buy them out? And what are his surprising conditions?"--Back cover.